Idiopathic Scoliosis: Novel Challenges for Researchers and Clinicians - Fabio Zaina; Sabrina Donzelli; Stefano Negrini (MDPI AG, 2023)
Scoliosis is a three-dimensional deformity of the spine and trunk [...]